Suppressor of fused associates with dissemination patterns in patients with glioma - Peris-Celda, María; Carrión-Navarro, Josefa; Palacín-Aliana, Irina; Sánchez-Gómez, Pilar; Acín, Ricardo Prat; Garcia-Romero, Noemi; Ayuso-Sacido, Angel (Frontiers in Oncology, 2022)
Gliomas are the most common brain tumors, which presents poor prognosis, due in part to tumor cells migration and infiltration into distant brain areas. However, the underlying mechanisms causing such effects are unknown. Hedgehog (HH)-Gli axis is one of the signaling pathways involved, with high number of molecular mediators. In this study, we investigated the association between HH-Gli intermediates and clinical parameters. We found that high level of SuFu is associated with high dissemination patterns in glioma patients. Therefore, we analyzed SuFu expression data in three glioma cohorts of surgical samples (N=1759) and modified its expression in Glioblastoma Cancer Stem Cells (GB CSCs) in vitro models. Our data reveal that SuFu overexpression increases cancer stemness properties together with a migratory phenotype. This work identifies SuFu as a new molecular player in glioma cell migration as well as a promising target to develop blocking agents to decrease GB dissemination.